Farmers’ Work-Life Quality and Entrepreneurship Will in China - Kong, Fan-Zhu; Zhao, Lily; Zhang, Xiao-Bing; Tsai, Cheng-Hung; Lin, David D. (Frontiers in Psychology, 2019)
New-generation farmers have become a vital force for entrepreneurship in their hometowns. To better promote farmers to start businesses, it’s important to know about their quality of work life. Based on a survey of the quality of work life and entrepreneurship will of farmers from three cities and eight counties in Shandong province of China, this paper analyzed the effects of farmers’ quality of work life on their entrepreneurship will in their hometowns using a Logistic regression model. Our findings show that farmers have a relatively low cognition level of their quality of work life, and their interpersonal relationship, work characteristics, material security, and family demands have significant effects on their entrepreneurship will. According to the findings, this paper proposed some suggestions for promoting farmers’ entrepreneurship will in their hometowns from the perspectives of organizational management, extrinsic entrepreneurship stimulus, and internal demand.